A comparison of calcium hydroxide/iodoform paste and zinc oxide eugenol as root filling materials for pulpectomy in primary teeth: A systematic review and meta‐analysis. Issue 3 (4th March 2019) - Najjar, Rahaf S.; Alamoudi, Najlaa M.; El‐Housseiny, Azza A.; Al Tuwirqi, Amani A.; Sabbagh, Heba J.
Abstract: Zinc oxide eugenol (ZOE) has traditionally been used as a root filling material in primary teeth pulpectomy. Calcium hydroxide and iodoform (Ca(OH)2 /iodoform) may have advantages as a root canal filling material to evaluate treatment success of Ca(OH)2 /iodoform pulpectomy in primary teeth compared with ZOE based on clinical and radiographical criteria. All human clinical studies reporting clinical and radiographical outcomes of Ca(OH)2/ iodoform compared with ZOE in primary teeth pulpectomy were identified in digital bibliographic databases. Two authors independently selected studies and extracted relevant study characteristics. Success of treatment was based on an accomplishment of specific clinical and radiographical criteria. Meta‐analyses were performed to appraise study heterogeneity and aggregated statistics. Out of 5, 000 articles identified in initial search, 15 articles met all inclusion criteria, while 10 were included in the meta‐analyses. At 6‐ and 12‐month follow‐up, there were no statistically significant differences in the clinical and radiographical success rates of Ca(OH)2 /iodoform and ZOE. However, ZOE was shown to have statistically significant higher success rates at ≥18‐month follow‐up. On the basis of the findings of this systematic review, we recommend that Ca(OH)2 /iodoform be utilized for pulpectomy in primary teeth nearing exfoliation; conversely, ZOE should be utilized when exfoliation is not expected to occur soon. Future randomized control clinical trials with a long‐term follow‐up are needed before a reliable conclusion can be drawn as to the best pulpectomy material. The success of pulpectomy in primary teeth depends on selecting the ideal root canal filling material. It is challenging to select the appropriate filling materials for primary teeth. ZOE or ZOE/iodoform combined with Ca(OH)2 appears to be the materials of choice if primary teeth are not nearing exfoliation. More high‐quality randomized control clinical trials with a long‐term follow‐up period are needed before a reliable conclusion can be drawn as to the best pulpectomy material in primary teeth (systematic review registration number: CRD42016037563).